Sensing the future of HCI: Touch, taste, and smell user interface - Obrist, M; Velasco, C; Vi, C; Ranasinghe, N; Israr, A; Cheok, A; Spence, C; Gopalakrishnakone, P (Association for Computing Machinery, 2016)
The senses we call upon when interacting with technology are restricted. We mostly rely on vision and hearing, and increasingly touch, but taste and smell remain largely unused. Although our knowledge about sensory systems and devices has grown rapidly over the past few decades, there is still an unmet challenge in understanding people’s multisensory experiences in HCI. The goal is that by understanding the ways in which our senses process information and how they relate to one another, it will be possible to create richer experiences for human-technology interactions.